Systematics and Multi-Gene Phylogeny of the Subfamily Nothoholostichinae (Ciliophora, Hypotrichia), With Integrative Description of a New Marine Species Nothoholosticha luporinii n. sp. - Zhang, Tengyue; Wang, Yurui; Cheng, Ting; Ma, Jiyang; Vd’ačný, Peter; Song, Weibo; Shao, Chen (Frontiers in Marine Science, 2020)
Morphogenesis of ciliated protists attracts a lot of attention, because their huge morphological diversity is related to formation of ciliary structures during cell division. In the present work, the morphology and morphogenesis as well as the phylogenetic position of a new, marine hypotrich ciliate, Nothoholosticha luporinii n. sp., were investigated. The new species is characterized by having a combination of the following features: a bicorona whose anterior row contains four frontal cirri and posterior row includes only two cirri, a single buccal cirrus, midventral complex composed of about 30 cirral pairs, one pretransverse cirrus, 3–6 transverse cirri, one left and one right marginal cirral row; three bipolar dorsal kineties; contractile vacuole located in about 2/3 of the body length, two types of cortical granules, and many macronuclear nodules scattered throughout the cytoplasm. The morphogenesis of N. luporinii follows the ontogenetic mode of Pseudokeronopsis, a well-known and closely related genus except that the macronucleus fuses into a single mass in the middle fission stage. Phylogenetic analyses based on the rDNA operon classify Nothoholosticha in the family Pseudokeronopsidae and support the distinctness of the new taxon as well as the monophyletic origin of the subfamily Nothoholostichinae.